BREAKING BAD NEWS IN A NEONATAL INTENSIVE CARE: THE PARENT'S EVALUATION - Ligia Marçola; Ivete Zoboli; Rita Tiziana Verardo Polastrini; Silvia Maria Macedo de Barbosa
ABSTRACT Objective: To describe the reports of parents of newborns (NB) with congenital malformations hospitalized in a Neonatal Intensive Care Unit (NICU) who received bad news, in order to identify the issues related to the perception of bad news given adequately or inadequately. Methods: A cross-sectional study was conducted from January to October 2018, in which parents of newborns with congenital malformations hospitalized in NICUs were interviewed at visiting hours, according to inclusion criteria. The questionnaire had semi-structured questions related to reception of bad news. Analysis of the data was descriptive. Results: 28 mothers and two fathers were interviewed and 16 (53.3%) reported having had at least one bad news in the NICU. Of those, 10 (62.5%) considered appropriate the way in which the news was given. The justifications were: sincerity of the professional, delicacy to give the news, giving hope to the family, use of appropriate words and demonstration of caring about the newborn. Six participants (37.5%) considered inadequate the way of breaking bad news. The reasons were: unpreparedness and lack of knowledge about the child's case, use of difficult language, haste or anxiety and discouragement of family hope. Most of the news was given by a professional alone, often by a medical resident. Conclusions: The communication of bad news was considered adequate by the parents, although this perception was not unanimous. This study, therefore, indicates that it is necessary to improve the communication of bad news in this NICU. Training professionals can assist in this process.